Preparation method and application of AKD composite MOF material

By combining the alkylkane dimer with Cu-MOF material and preparing the modified multi-layer structure AKD composite MOF material by hot pressing, the problem of difficulty in efficient recovery of SF6 in high humidity environment is solved, efficient adsorption and recovery of SF6 are achieved, and the mechanical strength and applicability of the material are improved.

CN119771372APending Publication Date: 2025-04-08BAISHAN POWER SUPPLY COMPANY OF STATE GRID JILIN ELECTRONICS POWER COMPANY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510149888.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recover SF6 from the N2/SF6 mixed gas under high humidity environments, and the MOF material is prone to hydrolysis or collapse in a wet environment, affecting its adsorption performance.

Method used

The AKD composite MOF material with a modified multilayer structure is prepared by combining alkylkane dimer (AKD) with Cu-MOF material by hot pressing, which improves its water vapor barrier properties and hydrophobic properties, thereby efficiently adsorbing SF6 under high humidity conditions.

Benefits of technology

It realizes efficient recovery of SF6 from N2/SF6 mixed gas under high humidity environment, improves the water vapor barrier and hydrophobic properties of the material, and has high mechanical strength, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771372A_ABST
    Figure CN119771372A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an AKD (Alkyl Ketene Dimer) composite MOF (Metal Organic Framework) material, and relates to a preparation method and application of a modified MOF material. The invention creatively provides a method for adsorbing SF6 by combining MOFs and alkyl ketene dimer under the condition of high humidity, and a novel modified multi-layer MOF material is prepared to realize high-selectivity adsorption of SF6 in an SF6 / N2 system. According to the invention, MOFs are introduced into the field of gas adsorption, and the MOFs adsorbent with specific recognition capability is prepared by utilizing the interaction among template molecules, metal ions and organic ligands. By ensuring the dry adsorption environment of MOFs, improving the adsorption effect of MOFs and realizing efficient recovery of SF6 from N2 / SF6 mixed gas, the invention adopts a simple and low-cost method, efficiently improves the water vapor barrier property and hydrophobic property, has higher mechanical strength, and can be applied to the industrial field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a modified MOF material. Background Art

[0002] Sulfur hexafluoride (SF6) gas is generally considered to be an inert gas. It is non-toxic, non-flammable, and has good physical and chemical stability as well as excellent dielectric and arc extinguishing properties. It is widely used in the cable industry. SF6 gas has excellent insulation properties and good thermal conductivity, and its performance far exceeds the currently commonly used air insulation medium. SF6 is used as an insulating medium in insulation equipment. Due to its own advantages, it can improve the performance and safety reliability of insulation equipment and reduce the size of the instrument. Nitrogen is commonly used in industry to purge SF6, which produces a mixed gas of N2 / SF6. Pure SF6 gas is expensive, which will cause expensive economic waste. At the same time, SF6 is a greenhouse gas. In the past 25 years, the average global concentration of sulfur hexafluoride has increased three times. SF6 is a potent greenhouse gas with a global warming capacity of 23,900 times that of CO2, and it remains stable in the atmosphere for about 3,200 years. Therefore, in the Kyoto Protocol adopted in 1997, SF6 was listed as a greenhouse gas together with N2O, CH4, and CO2. Therefore, how to select and recover SF6 from the N2 / SF6 mixed gas has attracted widespread attention from scholars.

[0003] Metal-Organic Frameworks (MOFs) are a class of crystalline materials composed of organic ligands and metal ions or metal clusters. Due to their large specific surface area, adjustable pore size, diversity of building blocks, and ease of chemical modification, they have different application prospects, such as gas storage, drug delivery, sensing, detection, catalysis and separation. In particular, they have natural advantages over traditional zeolite materials in the separation of light gases, and have therefore been favored in the past decade. Cu-MOF-OCH3 is a MOFs that has attracted much attention in recent years. The material has two micropore environments with different polarities, namely hydrophilic (high polarity) and hydrophobic (low polarity) pores. The hydrophilic pores have unsaturated metal sites, and the hydrophobic pores have CH groups. Based on the two different pore microenvironments of the material, the framework generates strong differences in the forces with SF6 molecules and N2, respectively. Therefore, the Cu-MOF-OCH3 material exhibits excellent separation performance for the separation of SF6-N2 mixtures. However, it is difficult to avoid water vapor and humid environments in industry, especially in southern cities in summer, where the relative humidity can even reach 90 RH. The practical applicability of MOF-based systems requires the water stability of the framework to be a prerequisite. In order to improve the hydrolytic stability of MOFs, three main strategies are used: (I) metal ions with high oxidation states, such as (Zr 4+ , Fe3+ , Al 3+ ,Cr 3+ ) with acid salt organic ligands, combined with or selected divalent metal ions, such as (Cu 2+ , Zn 2+ , Ni 2+ ) and ammonia donor spacers / ligands are used to construct MOFS, (II) increase the connectivity of organic linkers and inorganic nodes / clusters (III) incorporate hydrophobic parts into the skeleton by direct synthesis or by post-synthesis modification. However, the internal topological structure of MOFs is often changed by modifying different groups. The principle of MOFs to separate SF6 from the N2 / SF6 system is mainly due to the large van der Waals force of the internal pores (the van der Waals force of N2 is lower). Changing its pores may lose the current good selectivity or adsorption capacity. In addition, the functional groups that constitute the strong hydrophobic sites of MOFs also depend on the strength of the chemical bond force. The effect of long-term high humidity environment on the hydrophobic sites also needs to be studied. The present invention needs to fully consider the effect of the presence of gaseous water molecules on MOF. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention creatively proposes a method of combining MOFs with alkyl ketene dimer (AKD) to adsorb SF6 under high humidity (RH90) conditions, and prepares a new modified multilayer MOF material to achieve highly selective adsorption of SF6 in the SF6 / N2 system. The present invention introduces MOFs into the field of gas adsorption, and utilizes the interaction between template molecules and metal ions and organic ligands to prepare MOFs adsorbents with specific recognition capabilities. By ensuring a dry adsorption environment for MOFs, the adsorption effect of MOFs is improved, and efficient recovery of SF6 from a mixed gas of N2 / SF6 is achieved. The present invention adopts a simple and low-cost method to efficiently improve the water vapor barrier performance and hydrophobic performance, and has high mechanical strength, so that it can be used in the industrial field.

[0005] A method for preparing an AKD composite MOF material is specifically completed by the following steps:

[0006] 1. Preparation of Cu-MOF:

[0007] Cu(NO3)2·3H2O and 5-methoxyisophthalic acid were added to methanol, and ultrasonic treatment was performed until the solution became clear and transparent. Pyridine was then added, and the mixture was stirred and reacted at room temperature and pressure for a period of time. After the reaction was completed, the product was placed in a centrifuge tube for centrifugation, and the supernatant was discarded to obtain a blue solid reaction product, namely Cu-MOF.

[0008] 2. Multilayer modified MOF:

[0009] Cu-MOF is coated on a spunbond non-woven fabric, and then an alkyl ketene dimer emulsion is added to the spunbond non-woven fabric. After natural air drying, the fabric is cured at 120°C to 140°C for a period of time to obtain an AKD-MOF spunbond non-woven fabric. The AKD-MOF spunbond non-woven fabric is placed on a flat vulcanizer for hot pressing to obtain an AKD composite MOF material with a rough micro-nano surface structure.

[0010] Principle of the present invention:

[0011] Alkyl ketene dimer (AKD) is a material with high water vapor barrier in recent years. AKD itself is a low water-soluble compound. They can form a continuous chemical barrier layer in the polymer matrix, physically preventing the molecules of water vapor from passing through. In the present invention, AKD will cross-link with the MOF polymer matrix to increase the cross-linking density of the polymer, so that the movement between the polymer chains can be reduced, and the permeation rate of water vapor can be reduced. AKD has a certain polarity, and it forms hydrogen bonds or other intermolecular forces with the polar groups of MOF. These forces can enhance the barrier ability of the material to water vapor and do not affect the flux of non-polar SF6 and N2. The present invention can also improve its barrier properties by using hot pressing, and adopts a simple and low-cost method to hot press the spunbond nonwoven fabric under high temperature and high pressure conditions to form a micro-nano rough structure. The surface of the modified spunbond nonwoven fabric is very strong and wear-resistant. Even after repeated wear cycles, the spunbond fabric still maintains hydrophobicity.

[0012] The beneficial effects of the preparation method of a novel AKD composite MOF material of the present invention are embodied in:

[0013] Most conventional classic MOFs materials decompose or collapse in structure when exposed to water, and the introduction of hydrophobic sites will affect their saturated adsorption capacity or selectivity. Some MOFs with hydrophobic pores often have difficulty maintaining their structure in a long-term wet environment. The AKD layer wraps the Cu-MOF in it, and the AKD layer does not affect the gas flux of N2 and SF6. Its hydrophobic sites ensure the dry environment of the internal MOF, so that the adsorption and desorption efficiency of the MOF remains at the highest efficiency. In addition, since surfaces with high roughness are often fragile, the surface is easily contaminated and structurally damaged, which affects its superhydrophobic properties and water vapor barrier properties. The surface of the spunbond nonwoven fabric of the present invention has the advantage of extremely high wear resistance; and this spunbond fabric has a higher mechanical strength, and traditional MOF powder is easier to blow away. This higher mechanical strength makes this layered structure very suitable for industrial selection of SF6 gas recovery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The water vapor barrier performance diagram of the AKD composite MOF material prepared by changing the mass of the AKD emulsion in Examples 1 to 5;

[0015] Figure 2 The water contact angle diagram of the AKD composite MOF material prepared by changing the hot pressing treatment time in Examples 6 to 10;

[0016] Figure 3 The gas absorption performance diagram of the AKD composite MOF material prepared in Example 8 for repeated use is shown in which SF6 is selectively adsorbed from a mixed gas of N2 and SF6 at an air humidity of 90RH;

[0017] Figure 4 The gas absorption performance diagram of the AKD composite MOF material prepared in control example 1 for repeated use is shown in which SF6 is selectively adsorbed from a mixed gas of N2 and SF6 at an air humidity of 90RH. DETAILED DESCRIPTION

[0018] Specific implementation method 1: This implementation method is a method for preparing an AKD composite MOF material, which is specifically completed according to the following steps:

[0019] 1. Preparation of Cu-MOF:

[0020] Cu(NO3)2·3H2O and 5-methoxyisophthalic acid were added to methanol, and ultrasonic treatment was performed until the solution became clear and transparent. Pyridine was then added, and the mixture was stirred and reacted at room temperature and pressure for a period of time. After the reaction was completed, the product was placed in a centrifuge tube for centrifugation, and the supernatant was discarded to obtain a blue solid reaction product, namely Cu-MOF.

[0021] 2. Multilayer modified MOF:

[0022] Cu-MOF is coated on a spunbond non-woven fabric, and then an alkyl ketene dimer emulsion is added to the spunbond non-woven fabric. After natural air drying, the fabric is cured at 120°C to 140°C for a period of time to obtain an AKD-MOF spunbond non-woven fabric. The AKD-MOF spunbond non-woven fabric is placed on a flat vulcanizer for hot pressing to obtain an AKD composite MOF material with a rough micro-nano surface structure.

[0023] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the mass ratio of Cu(NO3)2·3H2O to methanol in step 1 is (10mmol-20mmol):(200mL-400mL). The other steps are the same as those in specific embodiment 1.

[0024] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the mass ratio of 5-methoxyisophthalic acid to methanol in step 1 is (10 mmol to 20 mmol): (200 mL to 400 mL). The other steps are the same as those in specific embodiment 1 or 2.

[0025] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the volume ratio of the mass of pyridine to methanol in step 1 is (10 mmol to 20 mmol): (200 mL to 400 mL). The other steps are the same as those of specific embodiments 1 to 3.

[0026] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the stirring reaction time at room temperature and pressure in step 1 is 10 h to 12 h. The other steps are the same as those in specific embodiments 1 to 4.

[0027] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the mass fraction of alkyl ketene dimer in the alkyl ketene dimer emulsion described in step 2 is 90%. The other steps are the same as those of specific embodiments 1 to 5.

[0028] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the alkyl ketene dimer emulsion described in step 2 is 5% to 20% of the mass of Cu-MOF. The other steps are the same as those of specific embodiments 1 to 6.

[0029] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the curing time in step 2 is 0.5h to 1.5h, the hot pressing time in step 2 is 30s to 60s, and the hot pressing temperature is 140° C. The other steps are the same as those in specific embodiments 1 to 7.

[0030] Specific embodiment 9: This embodiment is an AKD composite MOF material used for selectively adsorbing SF6 from a mixed gas of N2 and SF6 in a high humidity environment.

[0031] Specific implementation method 10: This implementation method is different from specific implementation methods 1 to 9 in that the humidity of the high humidity environment is 80% to 90%. The other steps are the same as those of specific implementation methods 1 to 9.

[0032] The following examples are used to verify the beneficial effects of the present invention:

[0033] Examples 1 to 5 are for changing the mass of the alkyl ketene dimer emulsion in step 2 to determine the best effect, and Examples 6 to 10 are for changing the time of the hot pressing treatment in step 2 to determine the best effect.

[0034] Example 1: A method for preparing an AKD composite MOF material, which is specifically completed by the following steps:

[0035] 1. Preparation of Cu-MOF:

[0036] 15mmol Cu(NO3)2·3H2O and 15mmol 5-methoxyisophthalic acid were added to 300mL methanol, and ultrasonic treatment was performed until the solution became clear and transparent. Then 15mmol pyridine was added, and the mixture was stirred at room temperature and pressure for 12h. After the reaction was completed, the product was placed in a centrifuge tube for centrifugation, and the supernatant was discarded to obtain a blue solid reaction product, namely Cu-MOF.

[0037] 2. Multilayer modified MOF:

[0038] 5g of Cu-MOF was coated on a circular spunbond nonwoven fabric with a radius of 5cm, and then 0.25g of alkyl ketene dimer emulsion (AKD emulsion) was added to the spunbond nonwoven fabric, and then naturally air-dried and cured at 120°C for 1h to obtain AKD-MOF spunbond nonwoven fabric, where the AKD emulsion was 5% of the mass of Cu-MOF; the AKD-MOF spunbond nonwoven fabric was placed on a flat vulcanizer at a temperature of 140°C for hot pressing for 30s to obtain an AKD composite MOF material with a rough micro-nano surface structure;

[0039] The mass fraction of the alkyl ketene dimer in the alkyl ketene dimer emulsion in step 2 is 90%.

[0040] Comparative Example 1: The difference between this example and Example 1 is that in step 2, 0 g of alkyl ketene dimer emulsion is added to the spunbond nonwoven fabric, and after natural air drying, it is placed at 120° C. for curing for 1 h to obtain AKD-MOF spunbond nonwoven fabric, and the AKD emulsion is 0% of the mass of Cu-MOF. The other steps and parameters are the same as those in Example 1.

[0041] Example 2: The difference between this example and Example 1 is that in step 2, 0.5 g of alkyl ketene dimer emulsion is added to the spunbond nonwoven fabric, and after natural air drying, it is placed at 120° C. for curing for 1 h to obtain AKD-MOF spunbond nonwoven fabric, and the AKD emulsion is 10% of the mass of Cu-MOF. The other steps and parameters are the same as in Example 1.

[0042] Example 3: The difference between this example and Example 1 is that in step 2, 0.75 g of alkyl ketene dimer emulsion is added to the spunbond nonwoven fabric, and after natural air drying, it is placed in 120° C. for curing for 1 hour to obtain AKD-MOF spunbond nonwoven fabric, and the AKD emulsion is 15% of the mass of Cu-MOF. The other steps and parameters are the same as those in Example 1.

[0043] Example 4: The difference between this example and Example 1 is that in step 2, 1 g of alkyl ketene dimer emulsion is added to the spunbond nonwoven fabric, and after natural air drying, it is placed at 120°C for curing for 1 hour to obtain AKD-MOF spunbond nonwoven fabric, and the AKD emulsion is 20% of the mass of Cu-MOF. The other steps and parameters are the same as those in Example 1.

[0044] Example 5: The difference between this example and Example 1 is that in step 2, 1.25 g of alkyl ketene dimer emulsion is added to the spunbond nonwoven fabric, and after natural air drying, it is placed at 120° C. for curing for 1 h to obtain AKD-MOF spunbond nonwoven fabric, and the AKD emulsion is 25% of the mass of Cu-MOF. The other steps and parameters are the same as those in Example 1.

[0045] Example 6: A method for preparing an AKD composite MOF material is specifically completed by the following steps:

[0046] 1. Preparation of Cu-MOF:

[0047] 15mmol Cu(NO3)2·3H2O and 15mmol 5-methoxyisophthalic acid were added to 300mL methanol, and ultrasonic treatment was performed until the solution became clear and transparent. Then 15mmol pyridine was added, and the mixture was stirred at room temperature and pressure for 12h. After the reaction was completed, the product was placed in a centrifuge tube for centrifugation, and the supernatant was discarded to obtain a blue solid reaction product, namely Cu-MOF.

[0048] 2. Multilayer modified MOF:

[0049] 5g of Cu-MOF was coated on a circular spunbond nonwoven fabric with a radius of 5cm, and then 0.75g of alkyl ketene dimer emulsion (AKD emulsion) was added to the spunbond nonwoven fabric, and then naturally air-dried and cured at 120°C for 1h to obtain AKD-MOF spunbond nonwoven fabric, where the AKD emulsion accounted for 15% of the mass of Cu-MOF; the AKD-MOF spunbond nonwoven fabric was placed on a flat vulcanizer at a temperature of 140°C for hot pressing for 10s to obtain an AKD composite MOF material with a rough micro-nano surface structure;

[0050] The mass fraction of the alkyl ketene dimer in the alkyl ketene dimer emulsion in step 2 is 90%.

[0051] Example 7: This example is different from Example 6 in that in step 2, the AKD-MOF spunbonded nonwoven fabric is placed on a flat vulcanizer at a temperature of 140° C. for hot pressing for 15 seconds. The other steps and parameters are the same as those in Example 6.

[0052] Example 8: The difference between this example and Example 6 is that in step 2, the AKD-MOF spunbonded nonwoven fabric is placed on a flat vulcanizer at a temperature of 140° C. for hot pressing for 30 seconds. The other steps and parameters are the same as those in Example 6.

[0053] Example 9: The difference between this example and Example 6 is that in step 2, the AKD-MOF spunbonded nonwoven fabric is placed on a flat vulcanizer at a temperature of 140° C. for hot pressing for 45 seconds. The other steps and parameters are the same as those in Example 6.

[0054] Example 10: This example is different from Example 6 in that in step 2, the AKD-MOF spunbonded nonwoven fabric is placed on a flat vulcanizer at a temperature of 140° C. for heat pressing for 60 seconds. The other steps and parameters are the same as those in Example 6.

[0055] Hot embossing is a conventional method for preparing regular microstructure surfaces. It generally refers to a low-cost and fast method for replicating specific structural patterns at the micro-nano scale. The principle is to use the thermoplastic characteristics of polymer materials and pressurize the substrate at a certain temperature to fill the microstructure area on the motherboard, thereby realizing the replication and transfer of the structural pattern to the polymer surface. Hot embossing can obtain high-resolution, high-aspect-ratio structures with flexible methods and high accuracy. In the present invention, hot pressing treatment can increase the roughness of the surface of AKD spunbond fibers, thereby improving the long-term water vapor barrier and dust-repelling effect of AKD-MOF spunbond fabrics.

[0056] Figure 1 The water vapor barrier performance diagram of the AKD composite MOF material prepared by changing the mass of the AKD emulsion in Examples 1 to 5;

[0057] Figure 2 The water contact angle diagram of the AKD composite MOF material prepared by changing the hot pressing treatment time in Examples 6 to 10;

[0058] from Figure 1 and Figure 2 It can be seen that the AKD emulsion with a mass of 15% of the mass of Cu-MOF and a hot pressing treatment time of 30 seconds shows a good water contact angle. It is worth noting that when the AKD mass ratio exceeds 15%, its water vapor barrier property changes very slowly, and when the hot pressing treatment time exceeds 30 seconds, the hydrophobicity begins to decrease. This may be because the structure between the screen and the spunbond fabric is destroyed due to the excessively long hot pressing treatment time.

[0059] Adsorption test:

[0060] The AKD composite MOF material prepared in Example 8 was used to selectively adsorb SF6 from a mixed gas of N2 and SF6 (the volume fraction of SF6 was 10%) at an air humidity of 90 RH. The adsorption was repeated ten times under this condition. The adsorption amount was shown in FIG. Figure 3 As shown;

[0061] Figure 3 The gas absorption performance diagram of the AKD composite MOF material prepared in Example 8 for repeated use is shown in which SF6 is selectively adsorbed from a mixed gas of N2 and SF6 at an air humidity of 90RH.

[0062] Figure 3 Repeated experiments were conducted on the AKD composite MOF material, which was repeated ten times in a humid environment. After adsorption and desorption, it was found that the adsorption performance of the material had no obvious effect and was maintained at a very high adsorption level, which shows that the material has excellent reusability and hydrophobic effect.

[0063] Figure 4 The gas absorption performance diagram of the AKD composite MOF material prepared in the control example 1 for repeated use, in which SF6 is selectively adsorbed from a mixed gas of N2 and SF6 at an air humidity of 90RH;

[0064] contrast Figure 3 and Figure 4 It can be seen that the reuse ability and hydrophobic effect of the AKD composite MOF material prepared in Example 8 are better than those of the AKD composite MOF material prepared in Control Example 1.

Claims

1. A method for preparing an AKD composite MOF material, characterized in that The method is specifically completed according to the following steps:

1. Preparation of Cu-MOF: Cu(NO3)2·3H2O and 5-methoxyisophthalic acid were added to methanol, and ultrasonic treatment was performed until the solution became clear and transparent. Pyridine was then added, and the mixture was stirred and reacted at room temperature and pressure for a period of time. After the reaction was completed, the product was placed in a centrifuge tube for centrifugation, and the supernatant was discarded to obtain a blue solid reaction product, namely Cu-MOF.

2. Multilayer modified MOF: Cu-MOF is coated on a spunbond non-woven fabric, and then an alkyl ketene dimer emulsion is added to the spunbond non-woven fabric. After natural air drying, the fabric is cured at 120°C to 140°C for a period of time to obtain an AKD-MOF spunbond non-woven fabric. The AKD-MOF spunbond non-woven fabric is placed on a flat vulcanizer for hot pressing to obtain an AKD composite MOF material with a rough micro-nano surface structure.

2. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The mass ratio of Cu(NO3)2·3H2O to methanol in step 1 is (10mmol-20mmol):(200mL-400mL).

3. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The mass ratio of 5-methoxyisophthalic acid to methanol in step 1 is (10 mmol to 20 mmol): (200 mL to 400 mL).

4. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The volume ratio of the mass of pyridine and methanol described in step 1 is (10mmol-20mmol):(200mL-400mL).

5. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The stirring reaction time at normal temperature and pressure in step 1 is 10 h to 12 h.

6. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The mass fraction of the alkyl ketene dimer in the alkyl ketene dimer emulsion in step 2 is 90%.

7. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The alkyl ketene dimer emulsion described in step 2 is 5% to 20% of the mass of Cu-MOF.

8. The method for preparing an AKD composite MOF material according to claim 1, characterized in that The curing time in step 2 is 0.5h to 1.5h; the hot pressing time in step 2 is 30s to 60s, and the hot pressing temperature is 140°C.

9. Application of an AKD composite MOF material prepared by the preparation method according to claim 1, characterized in that An AKD composite MOF material is used for selectively adsorbing SF6 from a mixed gas of N2 and SF6 in a high humidity environment.

10. The use of an AKD composite MOF material as claimed in claim 2, characterized in that The humidity of the high humidity environment is 80% to 90%.